2006
DOI: 10.1590/s0102-86502006001000003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simvastatin in abdominal sepsis in rats<A NAME="volta1"></A>

Abstract: Purpose: Statins are widely recognized as hypolipemic drugs, but some studies have observed anti-inflammatory and immunomodulatory effects, known as pleiotropic. The aims of this work was to study possible anti-inflammatory effects of simvastatin in abdominal sepsis. Serum pro-inflammatory cytokines and leukocytes count were determined in an experimental model of abdominal sepsis, using cecal ligation and puncture (CLP) in rats. Methods: Twenty eigth Wistar rats weighing 285±12g were randomly divided in: CLP/S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 42 publications
1
17
0
1
Order By: Relevance
“…The results showed that TNF-α, IL-1β and IL-6 values in septic group previously treated with simvastatin were significantly lower than in the untreated sepsis group. The same occurred in total leukocytes and neutrophils 14 . In another study, our group showed that simvastatin also had important anti-inflammatory action in the abdominal sepsis in diabetic rats.…”
Section: Discussionsupporting
confidence: 57%
“…The results showed that TNF-α, IL-1β and IL-6 values in septic group previously treated with simvastatin were significantly lower than in the untreated sepsis group. The same occurred in total leukocytes and neutrophils 14 . In another study, our group showed that simvastatin also had important anti-inflammatory action in the abdominal sepsis in diabetic rats.…”
Section: Discussionsupporting
confidence: 57%
“…It has been also demonstrated that statin decreases the expression of cytokines 26 . Moreover, recent experimental studies have demonstrated the antiinflammatory action of statins in improving the healing of infected wounds in rats 6 , as well as in abdominal sepsis 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Statins have been shown to be especially effective in reducing low-density lipoprotein cholesterol (LDL) and, to a lesser extent, triglyceride levels 2 . Statins' antiinflammatory effects have been proposed not only to reduce cardiovascular disease, but also to help improve other conditions that are not influenced by lipid levels, including rheumatoid arthritis 3 , stroke 4 , graft rejection 5 and infection 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that simvastatin increases the survival of patients with sepsis or infection by inhibiting sepsis-induced mortality and preventing acute kidney injury (12). It has also been demonstrated that induces anti-inflammatory effects in abdominal sepsis (13). Furthermore, simvastatin treatment improves the survival rate in a murine model of burn sepsis by elevating interleukin (IL)-6 levels (14).…”
Section: Introductionmentioning
confidence: 99%